Educational Content in Japanese Manga: Learning Science, History, and Ethics through Pop Culture - Rohmah, Naila; Rosyidha, Alfin (Vocational College of Diponegoro University, 2025)
This study explores the educational potential of Japanese manga by analyzing how academic and ethical content is embedded within three selected titles: Cells at Work!, Showa: A History of Japan, and Death Note. Using a qualitative content analysis approach, the research examines how these works convey knowledge across the domains of science, history, and ethics through narrative and visual storytelling. Findings reveal that manga can promote scientific literacy, foster historical empathy, and stimulate moral reasoning by integrating cognitive and affective learning in accessible formats. The study highlights manga’s interdisciplinary relevance and its capacity to function as a pedagogical tool in both formal and informal educational settings. These results underscore manga’s role not only as a form of entertainment but as a culturally responsive medium for critical and character education. Implications for educators, researchers, and curriculum designers are discussed, with recommendations for further exploration of manga’s integration into diverse learning environments